Will They Stay or Will They Go? Examining the Brain Drain in Canada's Provincial North. (17th May 2020) - Hillier, Cathlene; Sano, Yujiro; Zarifa, David; Haan, Michael
Abstract: Brain drain is an increasingly important concern for local governments in northern communities in Canada in maintaining and enhancing human capital levels to sustain vibrant economies and communities. Researchers, however, have yet to examine the magnitude of north‐south out‐migration nor do we know the characteristics of youth who are likely to relocate. Our study contributes to this knowledge gap by employing multiple waves from Statistics Canada's Youth in Transition Survey (Cohort A) linked to each youth's reading scores from the Programme for International Student Assessment (measured at age 15), and longitudinally to their tax filer information until age 30 (T1 Family Files). Résumé: La fuite des cerveaux est une préoccupation de plus en plus importante pour les gouvernements locaux des collectivités du Nord du Canada dans le maintien et l'amélioration des niveaux de capital humain afin de soutenir des économies et des collectivités dynamiques. Toutefois, les chercheurs n'ont pas encore examiné l'ampleur de l'émigration nord‐sud et nous ne connaissons pas non plus les caractéristiques des jeunes susceptibles de déménager. Notre étude contribue à ce manque de connaissances en utilisant de multiples ondes de l'Enquête sur les jeunes en transition (cohorte A) de Statistique Canada liées aux résultats de lecture de chaque jeune du Programme international de lecture du suivi des élèves (mesurés à l'âge de 15 ans), et longitudinalement à leurs informations de déclarant jusqu'à l'âge 30 (T1 Family Files).